PREPARATION AND OPTIMIZATION OF CILOSTAZOL NANOEMULSION ORAL LIQUID DOSAGE FORM - AL-SHAIBANI, ABULFADHEL JABER NEAMAH; AL-GBURI, KARRAR; ALBO HAMRAH, KARRAR TALIB KHUDHAIR (International Journal of Applied Pharmaceutics, 2023)
Objective: Cilostazol has poor water solubility and low oral bioavailability. Therefore, the formulation of cilostazol as a nanoemulsion may enhance its solubility and improve oral bioavailability. Hence, the aim of this study was to formulate and characterize an oil-in-water (o/w) nanoemulsion of cilostazol as an oral liquid dosage form. Methods: Pseudo-ternary phase diagrams were constructed using the aqueous titration method. Formulations of pseudo-ternary phase plots consisting of oil, various weight ratios of S mix (mixture of surfactant and co-surfactant), and deionized water were made. Different characterization studies, droplet size measurement, polydispersity index, drug content, zeta potential measurement, and in vitro release have been conducted to choose the optimized formula. Results: The characterization studies have demonstrated that the optimized formula is (F-6), consisting of 20 % S mix (3:1), 10% ginger oil, and 70% deionized water. This formula had the following characteristics; droplet size (72.9-110 nm), polydispersity index (0.22), percentage of drug content (99.8%), and in vitro release of cilostazol nanoemulsion was significantly higher (P<0.05) in comparison with other formulations. A Scanning probe microscopy (SPM) study has revealed that the droplet size of F-6 was at the nano-scale. Conclusion: In conclusion, the optimized cilostazol formula (F-6) is a promising formula which may have the capability of improving the oral bioavailability of cilostazol.